Kindlin-3-mediated signaling from multiple integrin classes is required for osteoclast-mediated bone resorption - Schmidt, Sarah; Nakchbandi, Inaam; Ruppert, Raphael; Kawelke, Nina; Hess, Michael W.; Pfaller, Kristian; Jurdic, Pierre; Fässler, Reinhard; Moser, Markus (The journal of cell biology, 2011)
The blood cell-specific kindlin-3 protein is required to activate leukocyte and platelet integrins. In line with this function, mutations in the KINDLIN-3 gene in man cause immunodeficiency and severe bleeding. Some patients also suffer from osteopetrosis, but the underlying mechanism leading to abnormal bone turnover is unknown. Here we show that kindlin-3-deficient mice develop severe osteopetrosis because of profound adhesion and spreading defects in bone-resorbing osteoclasts. Mechanistically, loss of kindlin-3 impairs the activation of β1, β2, and β3 integrin classes expressed on osteoclasts, which in turn abrogates the formation of podosomes and sealing zones required for bone resorption. In agreement with these findings, genetic ablation of all integrin classes abolishes the development of podosomes, mimicking kindlin-3 deficiency. Although loss of single integrin classes gives rise to podosomes, their resorptive activity is impaired. These findings show that osteoclasts require their entire integrin repertoire to be regulated by kindlin-3 to orchestrate bone homeostasis.
Gesehen am 28.06.2021